2009
DOI: 10.1016/j.jnucmat.2009.01.117
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the influence of plasma properties and SOL transport on the particle flux profiles on divertor plates in the Large Helical Device

Abstract: Particle flux profiles on the divertor plates and the electron temperature profiles in the scrape-off layer (SOL) in the Large Helical Device (LHD) heliotron were investigated with EMC3-EIRENE code. These profiles are modified during a discharge due to the changes of the edge plasma density and temperature those can cause the change of transport coefficient.Comparison of the edge electron temperature profiles between the measurements and the simulations revealed that the cross field transport coefficients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…We have done some analysis on the parameter dependence of perpendicular transport coefficients in ref. [40,41]. In ref.…”
Section: The Stochastic Layer Of Lhdmentioning
confidence: 99%
“…We have done some analysis on the parameter dependence of perpendicular transport coefficients in ref. [40,41]. In ref.…”
Section: The Stochastic Layer Of Lhdmentioning
confidence: 99%
“…The plasma experiments have been conducted under two divertor configurations in LHD. One is the helical divertor (HD) [2][3][4][5][6][7][8][9][10] and the other is the local island divertor (LID) [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The particle and heat load distributions on the divertor have been investigated in the HD configuration in LHD, and it has been revealed that the distributions are non-uniform in both toroidal and poloidal directions [2,3]. Comparison of the experimental observation and the field lines tracing calculation shows that the magnetic field line structure on the divertor dominates the distributions rather than the plasma transport [3,10]. The magnetic field line structure can be visualized by using the profiles of the connection length of magnetic field lines (L c ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of mechanisms of determining heat flux and its profile on divertor plates is necessary for the design. In the Large Helical Device (LHD), the largest heliotron-type superconducting device, particle and heat deposition profiles on the divertor plates have been investigated by using Langmuir probes, thermocouples and an infrared camera [1][2][3][4]. Unlike in the scrape-off layer in tokamaks with poloidal divertor configuration, field lines structure in the edge plasma region in LHD is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Operational conditions, such as density and heating power also affect the profiles in experiment, and it is considered to be caused by the changing of the balance of parallel and perpendicular transport. A Threedimensional plasma and neutral transport code, EMC3-EIRENE [10] has been applied to study edge transport in LHD [11], and comparisons of the edge electron temperature and particle flux profiles on divertor plates between the experimental observations and the numerical results have been conducted [4]. The results suggest that electron temperature affects edge diffusion properties larger than electron density, and the higher electron temperature the diffusion coefficients become large.…”
Section: Introductionmentioning
confidence: 99%